Chemical composition and in vitro digestibility of Stylosanthes guianensis varieties. (17th March 2014) - Li, Mao; Zi, Xuejuan; Zhou, Hanlin; Hou, Guanyu; Cai, Yimin
Abstract We evaluated the nutritive value of 10 varieties of stylo (Stylosanthes guianensis) in Hainan province, China, based on chemical composition and in vitro dry matter digestibility. Chemical composition of the varieties averaged 10.5% crude protein, 2.6% ether extract, 47.4% neutral detergent fiber, 39.7% acid detergent fiber and 0.59% total tannins. In vitro dry matter digestibility averaged 61.4%. The Relative Feed Value quality standard of individual varieties was grade 2 or higher, with the highest values for 'TPRC90028' and 'Reyan No. 2.' The results show that the stylo varieties have suitable nutritive values for livestock in tropical regions of China.